1995
DOI: 10.1002/ccd.1810340307
|View full text |Cite
|
Sign up to set email alerts
|

Balloon dilation of critical valvar pulmonary stenosis in the first month of life

Abstract: Between 1985 and 1992, 36 consecutive neonates, aged 1-29 days, weight 2.4-5.0 kg, with critical valvar pulmonary stenosis underwent attempted balloon dilation (BD). At catheterization, 30 were on prostaglandin (PGE1) therapy and 20 were intubated. The valve was successfully crossed and dilated in 34/36 (94%), including three with an echocardiographic diagnosis of valvar pulmonary atresia and a right ventricle of adequate size. The valve was first dilated with a 2- to 5-mm balloon and then with serially larger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0
5

Year Published

1997
1997
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 25 publications
1
21
0
5
Order By: Relevance
“…Several studies have shown that balloon dilatation is a good alternative to surgical treatment of critical pulmo- Pediatric Cardiology nary stenosis in neonates [3,5,6,12]. Premature infants and infants with low birth weight and critical pulmonary valve stenosis are a therapeutic challenge, since they encounter several specific problems, including avoidance of temperature loss during the procedure, venous access, and problems related to the small anatomical size of the cardiac structures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that balloon dilatation is a good alternative to surgical treatment of critical pulmo- Pediatric Cardiology nary stenosis in neonates [3,5,6,12]. Premature infants and infants with low birth weight and critical pulmonary valve stenosis are a therapeutic challenge, since they encounter several specific problems, including avoidance of temperature loss during the procedure, venous access, and problems related to the small anatomical size of the cardiac structures.…”
Section: Discussionmentioning
confidence: 99%
“…Further measurements, allowing us to obtain stable normothermia in our patient, were warming up of the catheterization laboratory, wrapping of the child in cotton, and additional covering of the extremities with aluminium foil. The 7-mm balloon catheter we used (Osypka, Grenzach-Whylen, Germany) proved ideal for the pulmonary valvuloplasty, since its low profile allowed it to be introduced through a 4 French sheath, thus avoiding the damage to the femoral vein that can be a major complication of balloon valvuloplasty [3,7,13]. Furthermore, due to the small diameter of the balloon catheter, a more time consuming multistep gradational approach using progressively larger balloons [3,5,11], or the application of a so-called transductal guidewire rail technique [8], were not necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Echocardiographic evaluations reveal average residual gradients of 15-20 mmHg. In reports where such data are available, between 10 and 20% of patients had doppler gradients over 30 mmHg [4,10]. Doppler evidence of moderate pulmonary insufficiency has been reported in perhaps 20% of cases at follow-up.…”
Section: Critical Pulmonic Stenosis In the Newbornmentioning
confidence: 95%
“…Patients have often been brought to the catheterization laboratory with a diagnosis of pulmonary atresia, found to have critical stenosis with tiny valve orifice, and undergone balloon dilation [4]. Given the successful outcome in these patients, it is not surprising that several groups attempted to develop techniques for crossing and dilating atretic pulmonary valves.…”
Section: Pulmonary Atresia In the Newbornmentioning
confidence: 99%